MicroRNAs Regulating Cytoskeleton Dynamics, Endocytosis, and Cell Motility—A Link Between Neurodegeneration and Cancer? - Gerasymchuk, Dmytro; Hubiernatorova, Anastasiia; Domanskyi, Andrii (Frontiers in Neurology, 2020)
The cytoskeleton is one of the most mobile and complex cell structures. It is involved in cellular transport, cell division, cell shape formation and adaptation in response to extra- and intracellular stimuli, endo- and exocytosis, migration and invasion. These processes are crucial for normal cellular physiology and are affected in several pathological processes, including neurodegenerative diseases and cancer. Some proteins, participating in clathrin-mediated endocytosis (CME), play an important role in actin cytoskeleton reorganization and formation of invadopodia in cancer cells and are also deregulated in neurodegenerative disorders. However, there is still limited information about the factors contributing to the regulation of their expression. MicroRNAs are potent negative regulators of gene expression mediating crosstalk between different cellular pathways in cellular homeostasis and stress responses. These molecules regulate numerous genes involved in neuronal differentiation, plasticity, and degeneration. Growing evidence suggests the role of microRNAs in the regulation of endocytosis, cell motility and invasiveness. By modulating the levels of such microRNAs, it may be possible to interfere with CME or other processes to normalize their function. In malignancy, the role of microRNAs is undoubtful, and therefore changing their levels can attenuate the carcinogenic process. Here we review the current advances in our understanding of microRNAs regulating actin cytoskeleton dynamics, CME and cell motility with a special focus on neurodegenerative diseases and cancer. We investigate whether current literature provides an evidence that microRNA-mediated regulation of essential cellular processes, such as CME and cell motility, is conserved in neurons and cancer cells. We argue that more research effort should be addressed to study the neuron-specific functions on microRNAs. Disease-associated microRNAs affecting essential cellular processes deserve special attention both from the view of fundamental science and as future neurorestorative or anti-cancer therapies.